Cloud‐Radiative Impact on the Regional Responses of the Midlatitude Jet Streams and Storm Tracks to Global Warming - Nicole Albern; Aiko Voigt; Joaquim G. Pinto (Journal of Advances in Modeling Earth Systems, 2019)
Abstract Previous work demonstrated the strong radiative coupling between clouds and the midlatitude circulation. Here we investigate the impact of cloud‐radiative changes on the global warming response of the midlatitude jet streams and storm tracks in the North Atlantic, North Pacific, and Southern Hemisphere. To this end, we use the ICOsahedral Nonhydrostatic global atmosphere model in present‐day setup and with the cloud‐locking method. Sea surface temperatures are prescribed to isolate the circulation response to atmospheric cloud‐radiative heating. In the annual mean, cloud‐radiative changes contribute one to two thirds to the poleward jet shift in all three ocean basins and support the jet strengthening in the North Atlantic and Southern Hemisphere. Cloud‐radiative changes also impact the storm track, but the impact is more diverse across the three ocean basins. The cloud‐radiative impact on the North Atlantic and North Pacific jets varies little from season to season in absolute terms, whereas its relative importance changes over the course of the year. In the Southern Hemisphere, cloud‐radiative changes strengthen the jet in all seasons, whereas their impact on the jet shift is limited to austral summer and fall. The cloud‐radiative impact is largely zonally symmetric and independent of whether global warming is mimicked by a uniform 4 K or spatially varying sea surface temperatures increase. Our results emphasize the importance of cloud‐radiative changes for the response of the midlatitude circulation to global warming, indicating that clouds can contribute to uncertainty in model projections of future circulations.